Nanoformulation prototype based on a natural extract for the potential treatment of type 2 diabetes mellitus (2022)
ABSTRACT: Triterpene-enriched fractions (OBE100) from Eucalyptus tereticornis demonstrated efficiency when administered intraperitoneally to diet-induced obesity (DIO) mouse model to treat obesity-related type 2 diabetes mellitus (T2DM)1; however, its oral administration has not yet led to satisfactory results. We aimed to develop an oral nano formulation that enhanced the promising effect of the OBE 100 fraction, guaranteeing higher stability and bioavailability of the pharmacologically active components present in the natural extract through the oral route.